Service Factors from Entrepreneurs’ View of Gem and Jewelry Business in Chanthaburi Province - Hanpakdeesakul, Sayomphoo; Bunnag , Nantharat; Suthiprabha, Teeravut (Asia Social Issues, 2025)
Service plays a critical role in the success and sustainability of businesses across diverse dimensions. Industries excelling in service provision possess the capacity to generate significant added value and ensure customer satisfaction. The gem and jewelry industry, particularly at the local level, stands out as a distinctive and intriguing business sector. This study aims to investigate service-related factors among gem and jewelry entrepreneurs in Chanthaburi province, conduct a comparative analysis of service opinions, and explore relationships and components impacting jewelry trade in the specific area. The research methodology involved in-depth interviews with 20 key informants, specifically local gem and jewelry business entrepreneurs. Participants were selected based on the precise physical locations of their businesses within the municipal area of Chanthaburi province. Findings indicate that a critical aspect of service provision lies in the service provider’s role as the direct communicator with consumers. These individuals must possess favorable qualities and behaviors to effectively deliver services, meeting the needs and expectations of customers. Furthermore, these service providers are pivotal in influencing the sales volume of gem and jewelry products.